Nurt historyzmu w dziewiętnastowiecznej biżuterii europejskiej - Letkiewicz, Ewa (Sztuka i Kultura, 2021)
19th-century references to the styles of the past epochs was not a discovery of the century. In 19th century, not for the first time – after the previous ‘renesances’ in European culture – the treasury of the past was looked into in search for inspiration and examples worth following. Inspirations by the past, repetitions of historic styles were so significant in the culture and science of 19th century that numerous later researchers were likely to consider it repetitive, eclectic, lacking originality. A closer look at the intentions of 19th-century artists brings about a conviction that the references to the styles of the past epochs did not result from a lack of ideas or invention but quite otherwise, from the discovery of the significance and strength of history. Not only did history itself become a large branch of humanistic knowledge in 19th century but – as written by Szymon Askenazy – also ‘one of the most important kind of public service’, and a historian dealing with this discipline came to embody more ‘than a simple, useful worker of his science’. He became a ‘good, indispensable servant of his nation’. History in the service of the nation triggered artistic phenomena unknown before. For the first time art was used as a weapon in the fight for the cause of the nation – understood as a group bound by common origin, common past, language, customs, religion. Jewellery has assumed an active role in the promotion of the ideology employing historical styles. Due to its small size contributing to mobility, it became an effective tool for the propagation of national ideas as early in the second quarter of 19th century. In search for examples worth following references were made to historical and archeological discoveries, ancient collections as well as – for the first time consciously – to the resources of folk art. The historicism current which swept the 19th-century Europe, regardless of its causes and character, was one of the most powerful forces shaping the unique forms of jewellery of the time.